Inducible Mosaic Cell Labeling Provides Insights Into Pancreatic Islet Morphogenesis - Freudenblum, Julia; Meyer, Dirk; Kimmel, Robin A. (Frontiers in Cell and Developmental Biology, 2020)
Pancreatic islets, discrete microorgans embedded within the exocrine pancreas, contain beta cells which are critical for glucose homeostasis. Loss or dysfunction of beta cells leads to diabetes, a disease with expanding global prevalence, and for which regenerative therapies are actively being pursued. Recent efforts have focused on producing mature beta cells in vitro, but it is increasingly recognized that achieving a faithful three-dimensional islet structure is crucial for generating fully functional beta cells. Our current understanding of islet morphogenesis is far from complete, due to the deep internal location of the pancreas in mammalian models, which hampers direct visualization. Zebrafish is a model system well suited for studies of pancreas morphogenesis due to its transparency and the accessible location of the larval pancreas. In order to further clarify the cellular mechanisms of islet formation, we have developed new tools for in vivo visualization of single-cell dynamics. Our results show that clustering islet cells make contact and interconnect through dynamic actin-rich processes, move together while remaining in close proximity to the duct, and maintain high protrusive motility after forming clusters. Quantitative analyses of cell morphology and motility in 3-dimensions lays the groundwork to define therapeutically applicable factors responsible for orchestrating the morphogenic behaviors of coalescing endocrine cells.